Świat zwierząt w wierszach Jana Twardowskiego i ich rosyjskich przekładach - Dworakowska, Beata Edyta (Acta Polono-Ruthenica, 2018)
In the present article a linguistic image of animals, excerpted from poems of Twardowski, compared with his translation to Russian are the object of analysis. The subject matter of the works concentrates on the most important existential problems and sacrum. Proposed analysis is located in investigative model of cultural linguistics which links to cognitive paradigm, while taking into account the strategies and techniques used translation. The monolingual analysis specified types and characteristics of animals, whereas bilingual analysis showed what happens with the linguistic image of love when it is transfered to other language, in this case to Russian language.